Spring's renewal - Gray, Shelley Shepard (New York : Avon Inspire, 2010)
Tim Graber arrives in Sugarcreek to help his aunt and uncle with spring planting. At first, Tim doesn't fit in with his many cousins and their crowded lifestyle. But when he meets Clara Slabaugh, the local school teacher, he understands why the Lord brought him to Sugarcreek.
Keywords: Amish -- Fiction; Floods -- Fiction; Love stories; Christian fiction